Achievement Goals, Fear of Failure and Self-Handicapping in Young Elite Athletes with and without Chronic Pain - Bodile Molenaar; Charlotte Willems; Jeanine Verbunt; Mariëlle Goossens (MDPI AG, 2021)
Background: Pain is a common problem in elite athletes. This exploratory study compares goal orientations towards sport, fear of failure, self-handicapping and pain catastrophizing between active young elite athletes with and without chronic pain (CP) complaints (longer than three months). It examines the associations between chronic pain, fear of failure, goal orientations, self-handicapping and pain catastrophizing in young elite athletes. We explore how far goal orientation can be explained by these factors. Methods: Young elite athletes completed an online questionnaire. Data analysis: Independent samples t-test, correlational analyses and multivariate regression analyses. Results: Participants were 132 young elite athletes (mean 16 years); data for 126 were analyzed. A total of 47% reported current pain, of which 60% had CP. Adolescents with CP showed significantly more pain intensity, fear of failure, self-handicapping and mastery-avoidance goals than those without. Pain intensity was significantly related to fear of failure, self-handicapping, pain catastrophizing and mastery-avoidance. Self-handicapping and fear of failure contributed significantly to mastery-avoidance variance. Performance-avoidance and -approach goals were explained by fear of failure. Conclusion: CP was common, with sufferers showing more fear of failure and self-handicapping strategies, and being motivated to avoid performing worse (mastery-avoidance). Self-handicapping and fear of failure influenced mastery-avoidance orientation, and fear of failure explained part of performance-avoidance and -approach orientations. Longitudinal studies should explore the role of these factors in the trajectory of CP in these athletes.